Investigation of Appropriate Adsorbents for Removal of Recalcitrants from Distillery Effluents: Exploring Effective Methods for Distillery Effluent Treatment (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The present study was conducted to find out the economic pollution reduction technique of distillery effluent that possesses a serious environmental problem. The distillery effluent is generally highly acidic (pH 3.8 - 4.4) with high rates of BOD 45000- 60000 mgl COD 70000 – 98000 mgl and also suspended solids (2000 -14000 mgl). Currently different treatment techniques are used to treat distillery effluent which includes fungal treatment, adsorption techniques, Electro sorption, filtration, biological treatment, etc. but no treatment method alone give the desired goal to treat the distillery effluent effectively and efficiently therefore further research study in this area should be carried out to prevent surface and ground water pollution.